開發「三件好事」手機行動應用程式與使用歷程分析 The Effectiveness of Developing "3 Blessings Exercise" on Mobile Application - 吳相儀 Hsiang-Yi Wu; 蔡佳伶 Jia-Ling Tsai; 黃玟臻 Wen-Zhen Huang (National Taiwan Normal University, 2024)
《三件好事APP》源自於正向心理學中快樂五練習介入方案，被發現是其中最有效的練習，可以增加快樂並降低憂鬱持續6個月。然而，研究上實行方式多採用紙本或簡單紀錄，國外幾款相關之行動應用程式（mobile application，簡稱APP）亦皆有其限制。研究目的：開發臺灣第一套《三件好事APP》手機APP並探究使用者之使用歷程，達到結合趣味記錄與分析回饋之成效。研究方法：先採焦點團體蒐集開發《三件好事APP》前之建議，開發完成後，徵求修習通識課程之學生自願使用，取使用成效最高者11人進行半結構式訪談，將所得資料進行內容分析。結果發現：本研究確實開發出《三件好事APP》，依據訪談內容將使用歷程編碼成五個主類目，分別為：一、認知：沉澱自我；二、情意：關注正向；三、實踐：內化養成；四、操作：快速便利；五、介面：回饋分析。最後，提出具體建議作為未來推廣與研究之參考。 "Three Good Things" is a practice originating from the five "happiness exercises" programs of positive psychology ,which include a Gratitude Journal, Three Good Things, Acts of Kindness, Optimistic Thinking, and Emotional Expression. "Three Good Things" is regarded as one of the most effective exercises (Seligman, 2005). This practice can increase happiness and reduce feelings of depression over 6 months. Most researchers of this practice have relied on paper-based or other simple techniques, such as communication software and mail, for recording responses (ex. Alexios et al., 2021; Luo et al., 2019; Sexton et al., 2019). Several limitations remain in terms of the adaptability and engagement with modern digital practices. To address these limitations, this study developed a fully Chinese-language APP called "3 Blessings Exercise" to explore user experience on mobile devices in Taiwan. Although several non-Taiwanese mobile apps enable users to record "Three Good Things," these apps have certain limitations. For example, many of these apps are not grounded in empirical research. In addition, they do not analyze user-provided data and do not promote habitual recording. These apps also do not remind users to make entries. Furthermore, the only app offering a Chinese interface is "Gratitude Journal," which structurally differs from the app developed in the current study. In this study, to enhance user engagement and feedback analysis, we developed an app that addresses these limitations by integrating and analyzing users' data. This APP employs the PERMA model (Seligman, 2011) for analysis, which covers Positive emotion, Engagement, positive Relationship, Meaning, and Accomplishment. This model enables users to recognize their sources of happiness and monitor their daily progress through graphical representations. To ensure that the app's design met users' requirements, insights were gathered from a focus group specializing in positive psychology. Upon completion, the app was rolled out to university students who had undertaken introductory courses on happiness and positive psychology who volunteered to try it. Semistructured interviews involving 11 participants were conducted to obtain feedback to enhance user experience. These participants were selected because they were the most engaged and reported the greatest benefits from the app. They had an average age of 19.9 years, with a standard deviation of 1.71 years. Data from the interviews were subjected to content analysis and categorized into five principal areas through process coding. As for the details of the focus group interviews which were conducted with current app users and experts in related fields before formal development. These interviews played a key role in identifying the following four major user requirements. First, the interface should be bright and clean, that is, designed to ensure simplicity and user-friendliness, with a gamified element involving plant cultivation to maintain user motivation. Second, text input should be the primary method for user recording. This enables users to make entries for the previous day, and it offers multiple reminders to ensure daily recordings. Some participants mentioned enjoying using different symbols to represent their daily moods while recording "Three Good Things" on paper. Therefore, we determined that adding mood icons could be useful. Third, although the main framework for record analysis is the PERMA model, general users may struggle with categorization based on this theoretical model. Thus, incorporating clear guidance or instructions is necessary. Fourth, the backend and output should be divided into two sections: student assignment requirements and researcher management requirements. Students can access their records through a web page to print their entries, whereas researchers can manage tasks in the backend through user accounts. We successfully transformed the core objective of the "Three Good Things" practice into a digital format that aligns with the preferences of modern users. We categorized the interview records obtained in this study into five main categories, with each representing a different aspect of user experience: 1. Cognitive (self-reflection and reshaping perspective): Emphasizing self-reflection and positive reinterpretation of daily events, the app encourages users to engage with personal experiences and obtain meaningful insights. By facilitating cognitive processing, the app helps users reshape their perceptions of everyday events and foster a more positive outlook on life. 2. Emotional (positive focus): The app's design effectively directs users' attention toward positive events, enabling them to not only record but also enhance their positive emotions. This functionality is essential for fostering an attitude of gratitude and appreciation for life and thereby improving emotional well-being. 3. Practice (internalization development): The app's core philosophy is centered on internalization of positive practices, that is, transforming fleeting moments of happiness into habitual behaviors. This transition from occasional experiences to consistent behavioral patterns is crucial for integrating positive psychology principles into users' daily routines, which enriches their life experiences. 4. Operation (quick and convenient): With an emphasis on user-friendliness, the app features a streamlined interface that simplifies the recording process. This focus on usability and accessibility ensures that users can easily incorporate the practice of logging their "Three Good Things" into their daily routines. 5. Interface (feedback analysis): The app's interactive tree-planting feedback mechanism provides users with a tangible representation of their progress and achievement. Despite the aforementioned achievements, such apps have room for further development and improvement. For example, the app of the present study was used only by university students, which limits its generalizability. In addition, given the importance of human interaction, we suggest adding social features to such apps. We also recommend that feedback features applicable to research-oriented perspectives be expanded. Furthermore, given that research on this topic remains in its exploratory phase, the rigor of the research designs for studies in this area can be improved. In summary, the development of the "3 Blessings" app represents a major advancement in the application of positive psychology practices to the digital field. This app not only seamlessly integrates the "Three Good Things" practice into a mobile device but also meets contemporary requirements for accessible and engaging tools for improving mental health. Overall, this study highlights the potential of mobile technology to enhance the effectiveness of psychological interventions, offering a promising direction for the development of technical applications in related fields. Further research and feedback are required to enhance our app's functionality and expand its effect on well-being and health in the evolving landscape of the digital age.